ANALYSIS OF TRANSFORMATION OF STRUCTURE MIGRATORY MOVEMENT OF THE POPULATION - Anastasia V. Vasilyeva; Leysan A. Davletshina; Alexey V. Puzakov (Статистика и экономика, 2016)
This article analyzes the migration ﬂows. Some details for the structure of migration in Russia. Calculations to assess the changes and shifts in the pattern ofmigration.